2015
DOI: 10.3892/or.2015.4419
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of apoptosis by proanthocyanidin-induced autophagy in the human gastric cancer cell line MGC-803

Abstract: Proanthocyanidins are flavonoids that are widely present in the skin and seeds of various plants, with the highest content in grape seeds. Many experiments have shown that proanthocyanidins have antitumor activity both in vivo and in vitro. Autophagy and apoptosis of tumor cells induced by drugs are two of the major causes of tumor cell death. However, reports on the effect of autophagy induced by drugs in tumor cells are not consistent and suggest that autophagy can have synergistic or antagonistic effects wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…However, in MGC‐803 human gastric cancer cells, PAs‐induced apoptosis was attenuated by PAs‐induced autophagy via reduction of PI3K/AKT/mTOR pathway, which was further confirmed by the addition of classical autophagy inhibitor 3‐methyladenine. After treatment with PAs (40.7 μg/mL) and 3‐methyladenine (5 mM), the inhibiton of autophagy by 3‐methyladenine could decrease Beclin 1 mRNA and increase Bcl‐2 mRNA, indicating that the block of PAs‐induced autophagy could significantly increase cell apoptosis …”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%
“…However, in MGC‐803 human gastric cancer cells, PAs‐induced apoptosis was attenuated by PAs‐induced autophagy via reduction of PI3K/AKT/mTOR pathway, which was further confirmed by the addition of classical autophagy inhibitor 3‐methyladenine. After treatment with PAs (40.7 μg/mL) and 3‐methyladenine (5 mM), the inhibiton of autophagy by 3‐methyladenine could decrease Beclin 1 mRNA and increase Bcl‐2 mRNA, indicating that the block of PAs‐induced autophagy could significantly increase cell apoptosis …”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%
“…Genetic ablation of Class III PI3K leads to reflective cellular and organ damage which epitomize the essential role in regulating functional autophagy. 23 Studies on knockdown of either Class III PI3K or Beclin1 showed the decreased formation of autophagosomes through downregulated expression of LC3BII, with concomitantly increased accumulation of p62, aggregation and lipidation of LC3, and polyubiquitinated proteins showed the significant role of Class III PI3K/Beclin1 complex. 24 The proautophagic effect of Beclin1 was inhibited by the Beclin1/ Bcl-2 complex through the attenuation of the oligomerization of Beclin1/Class III PI3K complex, thereby impeding the formation of autophagosomes.…”
Section: Discussionmentioning
confidence: 99%
“…This complex subsequently stimulates the formation of autophagosomes in the foam cells. Genetic ablation of Class III PI3K leads to reflective cellular and organ damage which epitomize the essential role in regulating functional autophagy . Studies on knockdown of either Class III PI3K or Beclin1 showed the decreased formation of autophagosomes through downregulated expression of LC3BII, with concomitantly increased accumulation of p62, aggregation and lipidation of LC3, and polyubiquitinated proteins showed the significant role of Class III PI3K/Beclin1 complex .…”
Section: Discussionmentioning
confidence: 99%
“…39 In addition, Chao Nie et al showed that procyanidins can induce autophagy in human gastric cancer cells but do not induce apoptosis. 40 In addition, Liao Fei showed that Euptox A has good antitumor activity. 41 Based on these data, we believe that Euptox A has the potential for use as a drug that promotes autophagy (similar to temozolomide) to kill apoptosis-resistant tumor cells by autophagic death.…”
Section: Discussionmentioning
confidence: 99%